PENGARUH KOMPETENSI AUDITOR DALAM MELAKUKAN AUDIT JUDGMENT TERHADAP KUALITAS AUDIT - Titik Sukmawati; Faisal Faisal (Diponegoro Journal of Accounting, 2015)
This study examines the effect of audit judgment competency to the audit quality performed by government external auditor. In this case, audit judgment competency was tested from three aspects, namely the audit expertise, accountability pressure, and the task complexity hypothesized to have an influence on audit quality.The respondents are the auditors of BPK RI. Sampling technic was using a random sampling method. Data are collected using survey questionnaires submitted directly to the respondents. From 200 questionnaires, only 113 questionnaires are used for analyzing. The data analysis was performed by regression analysis using the ordinary least square (OLS) methods.The results show that audit expertise and task complexity have a positive and significant effect on audit quality. While the accountability pressure has a negative and significant effect on audit quality.